2009
DOI: 10.1097/nen.0b013e3181a39b3f
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Development in a Baboon Model of Preterm Delivery

Abstract: Premature infants now have an improved chance of survival but the impact of respiratory therapies on the brain, particularly the cerebellum, remains unclear. We examined the effects of early nasal continuous positive airway pressure (EnCPAP) ventilation and delayed (Dn) CPAP on the development of the cerebellum in prematurely delivered baboons. The baboons were delivered at 125 ± 2 days of gestation and ventilated for 28 days with either EnCPAP commencing at 24 hours (n = 5) or DnCPAP commencing at 5 days (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 19 publications
4
23
1
Order By: Relevance
“…25 Bronchopulmonary dysplasia, a known risk factor for neurodevelopmental impairment, has also been reported to exert an effect on the granular cells of the cerebellum, as shown in a baboon model. 33 In the present study, however, bronchopulmonary dysplasia alone was not associated with severe cognitive and motor deficits, though the duration of O 2 requirement, which may have included a period of hyperoxia and hypoxia, was associated with poor cognitive and motor outcomes. Reports have shown that the use of either a high oxygen concentration, which affects the inner granular cell and Purkinje cell layer, 33 or a hypoxic insult, which affects neuronal migration, 41 could influence the growth of the developing human cerebellum.…”
Section: Discussioncontrasting
confidence: 37%
See 2 more Smart Citations
“…25 Bronchopulmonary dysplasia, a known risk factor for neurodevelopmental impairment, has also been reported to exert an effect on the granular cells of the cerebellum, as shown in a baboon model. 33 In the present study, however, bronchopulmonary dysplasia alone was not associated with severe cognitive and motor deficits, though the duration of O 2 requirement, which may have included a period of hyperoxia and hypoxia, was associated with poor cognitive and motor outcomes. Reports have shown that the use of either a high oxygen concentration, which affects the inner granular cell and Purkinje cell layer, 33 or a hypoxic insult, which affects neuronal migration, 41 could influence the growth of the developing human cerebellum.…”
Section: Discussioncontrasting
confidence: 37%
“…The rapid growth of the cerebellum that occurs from 28 -40 weeks of gestation can be impeded by premature birth. 7,32,33 Here, a smaller TCD, indicative of neuronal loss or impaired neuronal differentiation with a reduction in dendritic and axonal development that may be independent of immaturity, 3 was associated with poor cognitive and psychomotor function. These results concur with those of the report of Tich et al 34 in preterm infants born at a gestational age Ͻ30 weeks or a weight of Ͻ1.25 kg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rabbit anti-rat calbindin (1:500, Swant, Bellinzona, Switz) was used to identify Purkinje cells; rabbit anti-cow glial fibrillary acid protein (GFAP; 1:500, Sigma, St Louis, MO, USA) to identify astrocytes: mouse anti-human Ki-67 clone MIB-1 (1:100; DakoCytomation, Denmark) to identify mitotic cells; rat anti-bovine myelin basic protein (MBP, 1:100; Chemicon, USA) to assess the extent of myelination; rabbit anti-ionized calcium-binding adapter molecule 1 (Iba1, 1:1500, Wako Chemicals, Osaka, Japan) to identify microglia/macrophages, and rabbit anti-human p27 (Kip1) cyclin-dependent kinase inhibitor (1:1000, Millipore, Billerica, MA USA), to identify post-mitotic cells, as previously described (14). Control and experimental material was stained simultaneously to avoid procedural variation.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, we have reported an ontogeny of cerebral development similar to the human that shows abnormalities in postnatal growth and evidence for white and gray matter injury associated with neonatal intensive care, but not specific interventional therapies (25,44,62,64). More importantly, this model first demonstrated the neurological impact of mechanical ventilation on the preterm brain and the relative sparing effect of early noninvasive respiratory support (43,63,85). Other studies have demonstrated that this model also mimics the preterm human condition related to the occurrence of functional adrenal insufficiency and to adverse end-organ effects on the kidney and liver (33,40,41,73,93).…”
Section: -Day Model ("New" Bpd)mentioning
confidence: 94%